The Effect of Educational Video Media on Poetry Writing Skills of MA Hasan Muchyi Students - Anggraini, Camelia Nova; Sardjono; Sujarwoko (CV. Srikandi Kreatif Nusantara in collaboration with Institut Teknologi Mojosari Nganjuk, 2025)
This article examines the effect of using educational video media on improving the poetry writing skills of tenth-grade students at MA Hasan Muchyi. Initial observations indicated that students' poetry writing skills were low, with most students scoring below the minimum passing grade (75). This study employed an experimental method with a pre-test and post-test design in one group, where students were treated using educational video media. The results showed a significant improvement in students' poetry writing skills after the treatment. The average post-test score increased to 92.7, compared to the pre-test average of 84.2. Educational video media proved effective in boosting students' learning motivation and helping them understand key elements in writing poetry, such as diction, imagery, and figurative language. Furthermore, educational videos provided a more interactive and enjoyable learning environment, making it easier for students to grasp the material and enhance their creativity. Thus, this study concludes that the use of educational video media can significantly improve students' learning outcomes, particularly in poetry writing skills.